Factors that can be Supportive or Limiting in Nurturing Giftedness in Children - Yulduz Mansurova (Scientific Trends, 2024)
Giftedness in children goes beyond just having a high IQ—it includes creativity, emotional intelligence, and social awareness. This study explores what helps or hinders gifted children from reaching their potential. It dives into the roles of family support, stress, nutrition, and even technology in shaping their abilities. While challenges like academic pressure, social isolation, and limited opportunities can hold gifted children back, the right environment, proper nutrition, and personalized tools like AI can make a big difference. By understanding these factors, we can better support gifted kids to grow and thrive in all aspects of their lives.
Keywords: Gifted children, nurturing talent, child development, emotional well-being, family support, nutrition and cognition, stress and resilience, education.